Stress adaptation and ageing is controlled by senescence-inducing age-related changes in Arabidopsis thaliana : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology at Massey University, Palmerston North, New Zealand - Kanojia, Aakansha (Massey University, 2018)
Senescence is the final stage of leaf development and leads to the death of a leaf. In leaves, chloroplasts are the major source of nitrogen (75%-80%), which is found mainly in proteins. The disassembly of chloroplasts during the senescence process releases a considerable amount of nitrogen, which is then remobilized to other growing parts of the plant. Thus, nutrients from dying parts of the plants are crucial for the initial development of seeds and new plant organs. Therefore, while leaf senescence is a destructive process, efficient senescence also increases viability of the whole plant and its survival to the next season or generation. However, senescence can also be induced prematurely by abiotic stress. Early senescence caused by environmental stress can be undesirable as it may affect the growth and yield of a plant. Plants grown under abiotic stress conditions such as high salinity, drought, cold or heat, display a variety of molecular, biochemical and physiological changes. Plants under environmental stress conditions activate several signalling pathways which, in coordination with hormones such as ethylene and abscisic acid, allow for an adaptive response to stress, resulting in adjustments of plant growth and development, in an attempt to maximise survival chances. Early senescence of old leaves is one of the important strategies adapted by plants for the survival of young growing tissues. The remobilisation of nutrients from old leaves to young tissues allows survival of the whole plant under stressed conditions. However, the outcome of the stress, i.e. survival or death, depends on the strength and duration of the stress in combination with the stress response. A plant’s response to stressed conditions also depends on the age of the plant. It has been reported by multiple studies that the tolerance to stress decreases with age, however, the underlying molecular mechanisms are not well understood. In chapter 1, it is reviewed and proposed that plants of different age show distinct responses to environmental stress because of senescence-inducing age-related changes (ARCs). Research work in chapter 3 sought to understand the synchrony between ageing and reduction of plant stress tolerance, using Arabidopsis thaliana as a model plant. Transcriptomic studies were carried out to examine the occurrence of senescence-inducing ARCs in Arabidopsis first rosette early expanding leaves (EEL), mid expanding leaves (MEL) and fully expanded leaves (FEL). The transcriptomic dataset showed that, as the leaf grows, genes associated to DNA repair mechanisms are downregulated and genes linked to stress hormone biosynthesis, oxidative stress, senescence and other stress responses, are upregulated. This research confirmed that Arabidopsis young, mature and adult plants, when treated with drought, salt, and dark stresses, had greater stress sensitivity with increased age, consistent with the role of senescence-inducing ARCs in stress resistance. This study suggests that young plants are more tolerant to stress because of negligible senescence-inducing ARCs in young leaves, whereas the gradual accumulation of ARCs in mature leaves, and rapid accumulation in old leaves, results in decreased resistance to stress. Next, to characterise mutants that modulate senescence-induced ARCs, I used stress-sensitive onset of leaf death (old) mutants of Arabidopsis thaliana. The mutants were characterised based on stress responses observed in old13 and old14 mutant plants compared to the wild type (WT) (Chapter 4). The old13 mutant was selected as an appropriate mutant to study the regulatory pathway of senescence-inducing ARCs as I found that the old13 mutant plants are susceptible to stress in an age-dependent manner (Chapter 5). The transcriptomes of old13 leaves compared with the WT samples illustrate that stress susceptibility in the old13 mutant is because of early acquisition of senescence-inducing ARCs. Compared to the WT leaves, old13 showed significant downregulation of genes involved in antioxidant activity, stress tolerance, and cell-wall morphology, while genes involved in oxidative stress, senescence and stress responses were upregulated. Furthermore, transcriptional and metabolomic data illustrated that an unbalanced sugar level in old13 leaves is one of the important senescence-inducing ARCs involved in ageing and stress responses. Chapter 6 includes an attempt to identify the mutated gene in old13 using high throughput next generation sequencing. Further study on old13 gene recognition will offer an exciting opportunity to gain an in-depth knowledge of the coupling between ageing and stress responses in plants. Together, this study suggests that the occurrence of senescence-inducing ARCs is an intrinsic process integrated into the stress response and ensures certain death in plants.
Chapter 1 was published as: Kanojia, Aakansha, & Dijkwel, Paul P. (2018, April). Abiotic stress responses are governed by reactive oxygen species and age. Annual Plant Reviews Online 2018, Issue 1. https://doi-org.ezproxy.massey.ac.nz/10.1002/9781119312994.apr0611
Keywords: Arabidopsis thaliana -- Effect of stress on; Arabidopsis thaliana -- Aging; Plants -- Aging; Plant genetic regulation